PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Romadhani, Ahmad; Saifi, Muhammad; Nuzula, Nila Firdausi (FIA UB, 2020)
The purpose of this review is to find out the amounts of profit, company size, and dividend policy which can influence the company’s value. LQ45 which is listed in Indonesian Stock Exchange is in the year of 2015 – 2018. This research is using Explanatory Research with quantitative approach. The sampling technique is using purposive sampling. Profitability is a financial method used to gauge company’s profit. Company’s profit that comes from sales and investment return, can influence the company’s size. The company’s scale is an important information, used by investor who wants to invest their wealth to the company. The magnitude of company can influence dividend return. Company’s profit can affect the size of company and dividend return. It can be reflected in the increasing of company’ value. The performance of company can be a parameter used by investor to do an investment or funding to the company.